Hysterosalpingography in infertility - Bagaswoto Poedjomartono, Bagaswoto Poedjomartono (Universitas Gadjah Mada, 1984)
Hysterosalpingography is performed by injecting contrast media into the uterus to visualize the uterine cavity and Fallopian tubes. Water-soluble contrast media are used in these examinations. Hysterosalpingographic examination is very important for the diagnosis of infertility and some gynecologic abnormalities.Between January-December 1981 hysterosalpingography had been performed in 79 cases of primary infertility, 28 cases of secondary infertility and 3 cases with abortion history. The hysterosalpingogram demonstrated that 23.64% of all cases were bilateral non-patent and 21.8% unilateral non-patent. Hydrosalpinx was found in 22 cases, 17 cases with bilateral or unilateral non-patent tubes and 5 cases with patent ones. Ten cases showed paratubal filling assosiated with patent and non-patent tubes.Key Words: hysterosalpingography - hydrosalpinx - infertility - contrast media - Fallopian